ANALISIS PENGELOLAAN PIUTANG TERHADAP EFEKTIVITAS ARUS KAS PADA PT. PELABUHAN TANJUNG PRIOK CABANG PANJANG - Aisyah Rizkia; Mediya Destalia; M. Iqbal Harori (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to describe the analysis of accounts receivable management on the effectiveness of cash flow at PTPelabuhan Tanjung Priok Branch Panjang. This type of research is descriptive research using a qualitativeapproach. Sources of data in the research used are primary data and secondary data. Data collection techniquesare observation, interviews, and documentation. The results showed that the management of receivables carriedout by PT Pelabuhan Tanjung Priok Long Branch, namely collecting accounts receivable, conducting analysis ofaccounts receivable turnover (RTO) and collection of receivables (ACP), collecting trade receivables, confirmingaccounts receivable, making customer assessment standards using the method 5C, and provide credit terms toprospective borrowers. Based on the calculation results, it can be seen that the management of accounts receivableaffects the company's cash flow. It can be seen that the results of the calculation of receivables turnover (RTO) haveincreased every year and the results of the calculation of collection of accounts receivable (ACP) have decreasedevery year which indicates that the faster the proceeds can be collected back into cash. In this case, cash inflowshave increased due to payment of receivables from service users. So it can be concluded that wealth has arelationship with the company's cash flow.